Religious Orientation, Endorser Credibility, and the Portrayal of Female Nurses by the Media - Lin, Chyong-Ling (Journal of religion and health, 2015)
Medical consumption and media culture in Taiwan contain clear religious elements. It is common for people to believe that medicine is a supernatural treatment and to rely on thoughts of unseen power instead of rational consciousness. Religious-influenced patriarchy, seen in cultural gender roles, significantly influences religious adherents and degrades women as being part of a secondary class in society. As a contradictory tradition, women, in comparison to men, are considered best at undertaking certain jobs that require careful, detailed thought (such as nurses). Nursing and other occupations requiring a high degree of professionalism by women contradict the past religious-based concept of “ignorance is a woman’s virtue.” This study aims to probe female imagery in eastern and western Taiwan and explores whether religious culture and practice influences people’s cognition of female nurses in advertising. The constructs are analyzed through structural equation modeling. Results reveal that religious followers do not necessarily trust female nurses more just because they are portrayed as professional medical specialists. Most consumers reflect this negative cognition through purchase intentions of products. For example, in comparing portrayals of attractiveness with portrayals of professionalism, attractiveness results in a better advertising effect. People with intrinsic or extrinsic religious orientation have gradually lowered their negative impressions of women; however, religious followers still more strongly insist on women’s secondary position. Attractive female nurses are more likely judged as reliable, and this may be transferred to trust in their professional medical skills.